Impatiens jangjeonense (Balsaminaceae), a new species from South Korea - Oh, Ami; Oh, Byoung-Un; Oh, Hyun Kyung (Phytotaxa, 2024)
Impatiens jangjeonense (Balsaminaceae), a new species is reported from the mountainous regions of Gangwon-do province in South Korea. The plant shows morphological affinities with I. hambaeksanensis by means of elliptic or rhomboid-elliptic leaf blade, racemose inflorescence with erect rachises, and white or pinkish-white flower with yellowish and purplish spots, but differs from the latter by bigger flower 1.6–3.9 × 1.1–2 cm vs. 2–2.6 × 1.1–1.6 cm, and spur tip mainly 1- or 2-coiled and deeply biparted vs. mainly non-coiled and slightly biparted. Detailed description of the species along with its colored photographs are provided.